Public Policy Response in Expanding National Digital Education Access in Norway - Helene Knudstad; Liv Paulsengaard (Lafadz Jaya Publisher, 2025)
This study analyzes Norway's public policy responses in expanding national access to digital education. Drawing from policy documents, academic literature, and institutional practices, the paper explores how Norway integrates digitalization within its educational system while maintaining its longstanding commitment to equity. The findings are organized into four themes: national strategies, inclusion and accessibility, institutional readiness, and policy effectiveness. Norway has developed comprehensive digital education strategies that embed digital literacy into curricula, enhance teacher competencies, and ensure infrastructure support. Despite significant progress, challenges persist, especially in ensuring equitable access for students with disabilities, refugees, and those in remote areas. Institutional readiness varies, with universities and urban schools leading innovation, while vocational and rural institutions lag. Moreover, evaluation mechanisms often prioritize infrastructure over learning outcomes, leading to a policy-performance gap. The study concludes that while Norway’s approach offers a strong foundation, future success depends on adaptive governance, sustainable investment, and participatory policy-making that centers pedagogy and learner diversity. These insights contribute to broader debates on how advanced welfare states can ensure inclusive, effective, and future-ready digital education.